JJCO Best Reviewer Award (Japanese Journal of Clinical Oncology, 2020)
BACKGROUND: Terminally ill patients with cancer may have difficulty using Japan's public long-term care insurance system because functional decline often occurs rapidly near death. We examined care-need levels, service use, and factors associated with timely service use in this population. METHODS: We used anonymized long-term care insurance claims data from January 2018 to August 2025. Patients who died of cancer and whose first observed certification was granted within 1 year before death were included. Certification levels, certification period, and service use were described. Logistic regression examined factors associated with service use within 30 days after first certification. RESULTS: Among 10 491 patients, 17.8% were initially classified as support levels 1 and 2, and 62.0% were first certified within 3 months before death. Overall, 6740 (64.2%) used long-term care services during observation, and 4822 (46.0%) used services within 30 days. Compared with patients certified 6 to ≤ 12 months before death, those certified closer to death had higher odds of service use within 30 days: adjusted odds ratios were 1.63 (95% CI, 1.43-1.84) for ≤ 1 month, 1.23 (1.09-1.40) for 1 to ≤ 3 months, and 1.17 (1.02-1.34) for 3 to ≤6 months. Higher initial care-need levels were also associated with greater service use within 30 days, peaking at care-need level 2 (5.73; 4.78-6.88). CONCLUSIONS: Many patients were first certified shortly before death. Certification closer to death was associated with prompt service use, possibly reflecting urgent care coordination. Earlier information provision and timely certification may help patients access long-term care services before death.